High Resolution Single Particle Cryo-EM Refinement Using JSPR - Sun, Chen (Prog Biophys Mol Biol, 2020)
JSPR is a single particle cryo-EM image processing and 3D reconstruction software developed in the Jiang laboratory at Purdue University. It began as a few refinement scripts for symmetric and asymmetric reconstructions of icosahedral viruses, but has grown into a comprehensive suite of tools for building ab initio reconstructions, high resolution refinements of viruses, protein complexes of arbitrary symmetries including helical tubes/filaments, and image file handling utilities. In this review, we will present examples achieved using JSPR and demonstrate recently implemented features of JSPR such as multi-aberration “alignments” and automatic optimization of masking for the assessment of map resolution using “true” FSC.